Panthera Tigris and The Year of the Tiger: A Case Study Approach to Local NGO Strategies for Tiger Conservation in China - Piscopo, Stephen A (2010)
This study looks at localised strategies of international NGOs in China. China's exponential growth is unprecedented in scale and rate in comparison to any developing country and far eclipses that of any developed county. The conservation of wildlife is a worldwide phenomenon and since 'green issues' are as topical as ever the Chinese state and other range-states have come under criticism for its lack of enthusiasm. The introduction of this study outlines the basic problem of tiger conservation, placing it in a factual context and setting the scene for the activities of environmental NGOs. The literature review, after detailing the relevant tiger legislation, explores the major problems that the tiger species faces, such as prey depletion, habitat loss and conflict with humans. It then concentrates on the most recognised, debated and contentious threat of traditional Chinese medicine and industry. There is a long-standing and now illegal trade in tiger products that are sold on the traditional Chinese medicine market and China is known to sustain the biggest market for wildlife products. The use of wildlife products in traditional Chinese medicine is well documented and is a source of great conflict among different sides of society especially with the use and consumption of endangered species as health tonics and medicines. The literature review also examines enforcement issues, the nature of poaching, sums up the state of the tiger trade, reveals the growing force behind a petition to legalise the tiger trade and its critics. The tiger species is then placed in the context of Chinese culture and its image in Chinese history and folklore. The review closes with a look at the tiger conservation strategies already in place. The methodology used is case study research and is accompanied by the theoretical paradigm of critical postmodernism. The methodology is explained by its relevance to this particular study while other methods and theories are mentioned and critiqued. The study goes on to analyse the collected data focussing on strategy but also explains the phenomena which are expected to be found in case study research. The phenomena of the environmental NGO cases are explained as a web of complex relationships with a diverse cross section of the societal, economic and political realms. Then there is a chapter entitled ‘Critique of the Qualitative Research Process’. This described the fallibilities of the study, puts forward the debate surrounding qualitative research and strives to show awareness about a research study’s reliability and validity. By using introspective observation to view my own study broken down in its research process, I critiqued it and put forward recommendations for a successful piece of qualitative research. This study is concluded by looking back at the study as a process where inherent flaws were shown up and subsequently validated. It then discusses potential reasons as to how the study could have been improved. Finally it returns to the original focus of the study placing the tiger in the context of NGOs and tiger conservation and those clambering to do everything in their powerful to help such a wondrous species.